How Adaptation and User Engagement Affect Trust in Audio Guide Agents - Mari Saito; Seiji Yamada (IEEE Access)
This paper describes how user engagement affects users’ trust in audio guide agents to adapt to their environment. Audio guide agents are expected to be used more in the future because they can perform without interrupting the user’s actions. Because agents adapt to their environment and work collaboratively with users, trust in the agent is important. Therefore, we examined whether adaptation itself affects trust and whether intentional user operations as a means of user engagement affect trust. A participant experiment was conducted with two independent variables (the degree of adaptation to ambient noise and the availability of user operation), and the subjective evaluation of the impression of the agent was the dependent variable. For the factor of adaptability, agents with low and high noise-canceling performance were provided. For the factor of user engagement, a volume adjustment function for ambient noise was or was not provided. In an experimental laboratory environment where environmental sounds were controlled, it was verified that users perceive the agent as more intelligent and human-like only when the agent’s adaptation to the environment is low. However, agent adaptation increased trust in the agent, and user engagement also increased trust regardless of the agent’s adaptation level. On the other hand, in a real-world environment, adaptation tended to increase trust, but user engagement did not affect trust. This may be attributed to the impact of cognitive load on users in real environments, which could have hindered participants from operating as intended, even under conditions with operations. In systems where users and agents work collaboratively, the results suggest that intentionally increasing user engagement may increase trust in the agent when users are able to operate appropriately.